2021
DOI: 10.3390/molecules26206290
|View full text |Cite
|
Sign up to set email alerts
|

Natural Products and Their Derivatives against Human Herpesvirus Infection

Abstract: Herpesviruses establish long-term latent infection for the life of the host and are known to cause numerous diseases. The prevalence of viral infection is significantly increased and causes a worldwide challenge in terms of health issues due to drug resistance. Prolonged treatment with conventional antiviral drugs is more likely to develop drug-resistant strains due to mutations of thymidine nucleoside kinase or DNA polymerase. Hence, the development of alternative treatments is clearly required. Natural produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 186 publications
(294 reference statements)
0
5
0
Order By: Relevance
“…However, their molecular mechanisms of action have not been investigated adequately, and further studies are crucial to understand their efficacy in living organisms through in vivo studies. Few natural medicine products including berberine, manassantin B, grifolin, and triptolide have been tested both in vivo and in vitro in relation to the EBV antiviral and anticancer mechanisms) [ 80 ]. The summary of plants and natural bioactive compounds with antiviral effects against EBV is presented in Table 3 .…”
Section: Natural Products As Antiviral Agents Against Ebvmentioning
confidence: 99%
“…However, their molecular mechanisms of action have not been investigated adequately, and further studies are crucial to understand their efficacy in living organisms through in vivo studies. Few natural medicine products including berberine, manassantin B, grifolin, and triptolide have been tested both in vivo and in vitro in relation to the EBV antiviral and anticancer mechanisms) [ 80 ]. The summary of plants and natural bioactive compounds with antiviral effects against EBV is presented in Table 3 .…”
Section: Natural Products As Antiviral Agents Against Ebvmentioning
confidence: 99%
“…Reactivations continue to occur showing that the development of new alternative antiviral agents, with minimal side effects and reduced toxicity, plays a significant role in targeting different mechanisms. 58 The first antiviral used against HHV-1/2 viruses was idoxuridine, a nucleoside analogue capable of inhibiting viral nucleic acid synthesis, but, due to systemic toxicity, its use was limited. 59 Acyclovir is one of the most prescribed antivirals for the treatment of herpesvirus manifestations 19,20,25,27,60,61 being considered gold standard, 62,63 but this kind of drug, which inhibits viral replication at certain levels, has a narrow spectrum of action, does not act on latent viruses, causes undesirable side effects, and continued use may promote drug resistance.…”
Section: Antiviral Therapiesmentioning
confidence: 99%
“…To date, no effective herpesvirus vaccine has been found to completely eradicate the viral infection. Reactivations continue to occur showing that the development of new alternative antiviral agents, with minimal side effects and reduced toxicity, plays a significant role in targeting different mechanisms 58 …”
Section: Reviewmentioning
confidence: 99%
“…Natural products (NPs), obtained from components or metabolites of plants, animals, microorganisms etc., are widely used as drugs in the present era [4]. Numerous studies have demonstrated that NPs offer potent therapeutic strategies for various diseases, including cancer, diabetes, and immune diseases [5][6][7]. NPs such as curcumin and Quercetin possess anti-inflammatory and antioxidant effects while exhibiting fewer toxic and side effects, thus improving patient compliance [5].…”
Section: Introductionmentioning
confidence: 99%